FAKTOR – FAKTOR YANG MEMPENGARUHI PENGGUNAAN INFORMASI KINERJA DALAM LAKIP UNTUK PENGAMBILAN KEPUTUSAN (STUDI PADA PEMERINTAH KOTA AMBON) - Theophilia Fina Febrione Leiwakabessy; Max Hetharie (Soso-Q : Jurnal Manajemen, 2018)
This study aims to examine the effect of the quality of the performance measurement system, decision-making authority, support of internal stakeholders, external environment, individual perceptions of the use of performance information for decision making. The population in this study were Ambon City Government SKPD officials. The sampling method used is judgment sampling with a total sample of 66 respondents. Data analysis using multiple linear regression. The results showed that there were four factors that influence the use of performance information contained in the Government Agency Performance Accountability Report (LAKIP) Ambon City Government, namely the quality of information systems, support of internal stakeholders, external environment and individual perceptions of performance measurement system users, while factors the autonomy of decision making does not affect the use of performance information for decision making. Keywords: Government Agency Performance Accountability Report (LAKIP), information system quality, support of internal stakeholders, external environment and perception of the autonomy of decision making using performance information.